AFFECTIVE COMMITMENT AS A MEDIATION VARIABLES EFFECT OF EMPOWERING LEADERSHIP ON EMPLOYEE CREATIVITY - Alfaris, Belbi; Zakiy, Muhammad (Universitas Airlangga, 2021)
Leaders are very influential in shaping the creativity of employees in a company. This study aims to determine the effect of empowering leadership on employee creativity with affective commitment as a mediator. This research was conducted at five Islamic financial institutions in Yogyakarta. Respondents in this study amounted to 219 employees from a total of 5 Islamic financial institutions in Yogyakarta. This research uses descriptive quantitative methods with a Likert scale as its measurement. The data obtained were analyzed using Structural Equation Modeling (SEM) and to test the hypothesis using SmartPLS3.2. The results showed that empowering leadership has a positive effect on affective commitment, and empowering leadership has a positive effect on employee creativity. Affective commitment has a positive effect on employee creativity, and affective commitment mediates the positive influence of empowering leadership on employee creativity. Therefore, in creating employee creativity, leaders are needed to empower employees in making decisions in order to create the affective commitment from employees.